PENGARUH VARIASI KOMPONEN BIJI SAWIT TERHADAP HASIL TANGKAPAN IKAN SEPAT RAWA (Trichogaster trichopterus) PADA ALAT TANGKAP BUBU - Harsandi, Ari; Brown, Arthur; Syofyan, Irwandy (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was done in April 2015 in the open waters of Rimba MelintangVillage, Rokan Hilir Riau Province. The research objective was to determine theeffect of variations in the components of the palm kernel astringent (Trichogastertrichopterus) in fish traps catches. This research used 4 (four) comparison levels,were : Palm kernel bait (U1), Palm fruit fibersbait (U2), Palm kernel oil bait (U3),and mixture Palm fruit fibers and Palm kernel oil bait (U4). The catch device usedwere four unit of wire traps. The method used in this study was fishingexperiment in field. The design used was a simple design with randomization bait.From the result of research it can be concluded that type of palm kernel bait wasbring the best catches weight is 27.8 kilograms. This waters flow velocity in therange of 0.28-0.30 m/second and water temperature in the range of 28-30oC.Keyword : Traps, Bait, Catching